Faith and the presidency: from George Washington to George W. Bush - Smith, Gary Scott (Oxford University Press, 2006)
George Washington and providential agency -- Thomas Jefferson and the separation of church and state -- Abraham Lincoln : saving the last best hope of earth -- Theodore Roosevelt and the bully pulpit -- Woodrow Wilson : Presbyterian statesman -- Franklin Delano Roosevelt and the quest to achieve an abundant life -- Dwight David Eisenhower, dynamic conservatism, and the religious revival of the 1950s -- John F. Kennedy : the first Catholic president -- Jimmy Carter : first servant of the nation -- Ronald Reagan : making America God's shining city on a hill -- George W. Bush : a faith-based presidency